A low‐cost greenhouse‐based high‐throughput phenotyping platform for genetic studies: A case study in maize under inoculation with plant growth‐promoting bacteria. Issue 1 (21st April 2022) - Yassue, Rafael Massahiro; Galli, Giovanni; Borsato, Ronaldo; Cheng, Hao; Morota, Gota; Fritsche‐Neto, Roberto
Abstract: Greenhouse‐based high‐throughput phenotyping (HTP) presents a useful approach for studying novel plant growth‐promoting bacteria (PGPB). Despite the potential of this approach to leverage genetic variability for breeding new maize ( Zea Mays L.) cultivars exhibiting highly stable symbiosis with PGPB, greenhouse‐based HTP platforms are not yet widely used because they are highly expensive; hence, it is challenging to perform HTP studies under a limited budget. In this study, we built a low‐cost greenhouse‐based HTP platform to collect growth‐related image‐derived phenotypes. We assessed 360 inbred maize lines with or without PGPB inoculation under nitrogen‐limited conditions. Plant height, canopy coverage, and canopy volume obtained from photogrammetry were evaluated five times during early maize development. A plant biomass index was constructed as a function of plant height and canopy coverage. Inoculation with PGPB promoted plant growth in early developmental stages. Phenotypic correlations between the image‐derived phenotypes and manual measurements were at least 0.47 in the later stages of plant development. The genomic heritability estimates of the image‐derived phenotypes ranged from 0.23 to 0.54. Moderate‐to‐strong genomic correlations between the plant biomass index and shoot dry mass (0.24–0.47) and between HTP‐based plant height and manually measured plant height (0.55–0.68) across the developmental stages showed the utility of our HTP platform. Collectively, our results demonstrate the usefulness of the low‐cost HTP platform for large‐scale genetic and management studies to capture plant growth. Core Ideas: A low‐cost greenhouse‐based high‐throughput phenotyping platform was developed. Image‐derived phenotypes presented moderate to high genomic heritabilities and correlations. Plant growth‐promoting bacteria can improve plant resilience under nitrogen‐limited conditions.